Antimicrobial Polypeptides Capable of Membrane Translocation for Treatment of MRSA Wound Infection In Vivo. Issue 6 (10th December 2021) - Yang, Shengcai; Wang, Yanming; Tan, Jason; Teo, Jye Yng; Tan, Ko Hui; Yang, Yi Yan
Abstract: Multidrug resistant infections are plaguing the healthcare sector over the past few decades with limited treatment options. To overcome this problem, the authors synthesize a series of novel guanidinium‐functionalized polypeptides. Specifically, poly(l ‐lysine) (PLL) with different lengths is first synthesized by ring‐opening polymerization of N ε ‐benzyloxycarbonyl‐l ‐lysine‐ N ‐carboxyanhydride (Lys(Z)‐NCA) followed by functionalization with a guanidinium‐functional group to obtain guanidinium‐functionalized PLL (PLL‐Gua). To study the effect of hydrophobicity on antimicrobial activity, relatively more hydrophobic leucine‐NCA monomer or hydrophobic vitamin E moiety is introduced to PLL‐Gua. These polypeptides are characterized for antimicrobial activity against a panel of microbes including multidrug‐resistant bacteria, and hemolytic activity. Among all the polypeptides, PLL22 ‐Gua is most effective against bacteria and yeast. Particularly, excellent bactericidal activity is observed against Staphylococcus aureus and MRSA. PLL22 ‐Gua kills bacteria mainly by membrane translocation. In addition, PLL22 ‐Gua kills MRSA with low resistance frequency (<3.3 × 10 −8 ). In an MRSA‐caused wound infection mouse model, two‐day treatment (twice daily) with 10, 20, or 40 mg per kg of PLL22 ‐Gua shows up to 99.5% bacterial removal. Moreover, no acute dermal toxicity is observed even at a dose of 200 mg per kg. These promising results show the excellent potential of PLL22 ‐Gua as an antimicrobial agent against multidrug‐resistant infection in vivo. Abstract : Guanidinium‐functionalized polypeptides exhibit excellent activity especially against gram‐positive bacteria and yeast. The polypeptide with optimal compositions (PLL22 ‐Gua) kills bacteria predominantly via membrane translocation mechanism. MRSA shows extremely low resistance frequency to PLL22 ‐Gua treatment (<3.3 × 10 −8 ). PLL22 ‐Gua is demonstrated to be a potent antimicrobial agent in the treatment of MRSA‐induced wound infection, without inducing acute dermal toxicity.